Utilization of Open Source Application in Area of Augmented Reality Assembling Processes - Barna, Jozef; Fecova, Veronika; Novak-Marcincin, Jozef; Torok, Jozef (Manufacturing Technology Journal, 2012)
This chapter investigates the establishing process of virtual tool that in its logical core utilizes an approach based on the open source philosophy exploited for the work with the environment of augmented reality and its application in assembling processes. The traditional possibilities of how the engineer can use tools of augmented reality in form of normal commercial devices to collect the information about position of observed object in the working environment concern special devices with general structure formed by elements of motion tracking systems or technology of visual markers. In the beginning, the chapter briefly focuses on general problems in the application processes of virtual components and logical scripts in the area of the augmented reality. In following phase it provides fundamental philosophy and logical steps of new presented application of the augmented reality whereupon some samples can be provided created by means of logical operations and virtual elements from the open source environment. In the final step of this article chapter is clarified application process for creation and development of virtual software and hardware elements that are necessary for work in the augmented reality environment.
Keywords: Augmented Reality; Virtual environment; Open Source